Metabolic consequences of gonadotropin‐releasing hormone agonists vs orchiectomy: a randomized clinical study. (28th November 2018) - Østergren, Peter B.; Kistorp, Caroline; Fode, Mikkel; Bennedbæk, Finn N.; Faber, Jens; Sønksen, Jens
Abstract : Objectives: To compare the metabolic changes between men with advanced prostate cancer commenced on a gonadotropin‐releasing hormone (GnRH) agonist and those treated with orchiectomy. Patients and Methods: Fifty‐eight hormone‐naive men with advanced prostate cancer were randomly assigned (1:1) to either subcapsular orchiectomy or triptorelin 22.5 mg/24 week depot injections. The participants were followed for 48 weeks, with study visits at baseline, 12, 24 and 48 weeks. The primary endpoint was changes in fasting plasma glucose. Secondary endpoints included changes in body composition (i.e. weight, fat mass, visceral adipose tissue [VAT], subcutaneous adipose tissue [SAT], lean body mass [LBM] and android/gynoid fat [AG] ratio) assessed with dual X‐ray absorptiometry, serum lipid profiles, and insulin resistance evaluated during an oral glucose tolerance test. Linear mixed models were used to analyse the between‐group differences. Results: No treatment differences in the changes in fasting plasma glucose (0.2 mmol/L, 95% confidence interval [CI] −0.1, 0.4; P = 0.32) were observed. The orchiectomy group experienced greater increases in total fat mass (+2.06 kg, 95% CI 0.55, 3.56), SAT (+133 cm 3, 95% CI 22, 243) and weight (+3.30 kg, 95% CI 0.74, 5.87) at 48 weeks than did the triptorelin group (all P < 0.05), with the increases in fat mass being moderately correlated with increases in insulin resistance ( P < 0.001). No differences in changed VAT, LBM or AG ratio were observed between the groups. The pooled analyses, combining data from both groups, showed androgen deprivation therapy (ADT) to significantly increase fat mass, SAT, VAT, serum cholesterols (total, high‐density lipoprotein and low‐density lipoprotein) and all measures of insulin resistance over time, while LBM decreased as compared with baseline values (all P < 0.05). These changes were apparent after only 12–24 weeks of ADT. Conclusions: Androgen deprivation therapy leads to adverse changes in body composition and increased insulin resistance and serum cholesterols, with changes already observed after only 12–24 weeks of treatment. This study further demonstrates that orchiectomy causes greater increases in fat accumulation compared with GnRH agonists and that these increases are associated with an increase in insulin resistance.